Treatment of long bone fractures in children by elastic stable intramedullary nailing: Outcome and challenges in a unit with restricted technical platform - Eudes Ulrich Elvis Mahougnon Goudjo; Codjo Serge Metchihoungbe; Anani Komlan Mihluedo-Agbolan; Amoussou Sedjro Clotaire Romeo Houegban; Dede Virginie Teko; Octave Exupere Desire Dongmo Miaffo; Komla Gnassingbe (Wolters Kluwer Medknow Publications, 2023)
Introduction: Elastic stable intramedullary nailing (ESIN), developed by the Nancy school in France, is the gold standard for surgical treatment of long bone fractures in children. In Africa, few works have been devoted specifically to this technique. Objective: This study aimed to describe the outcome and to present the challenges with this technique in the treatment of long bone fractures in children. Patients and Methods: This was a prospective and descriptive study over 4 years including patients aged 0-15 years old operated using ESIN. Results: Sixty-two patients underwent ESIN, of whom 44 patients (70.96%) were for femur fractures, nine patients (14.52%) for tibia and fibula fractures and nine patients (14.52%) for humerus fractures. The majority of the patients treated with ESIN were children older than 6 years. Nine patients (14.51%) and 13 patients (20.98%) underwent ESIN following polytrauma and multiple fractures, respectively. Seven patients (11.29%) were operated on through-closed ESIN method. The unavailability of image intensifier (38.71%) and the presence of bone callus (40.32%) were the major reasons for using the open ESIN method. Thirty-three patients (53.23%) had minor or major complications. The majority of patients had satisfactory therapeutic outcomes. Conclusion: ESIN gives good results, even when the fracture site is approached.